Proceedings of the XXXII International Symposium on Multiparticle dynamics : Alushta, Crimea, Ukraine, 7-13 September 2002 - Sisaki͡an, A. N.; Kozlov, Guennadi; Kolganova, Elena (World Scientific, 2003)
This book covers a wide range of problems in elementary particle production physics - particle fluctuations and correlations, diffractive processes, soft and hard processes in quantum chromodynamics, heavy ion collisions, etc. Of the utmost importance are inclusion-theoretical papers devoted to the problems associated with high and even very high multiplicity particle production, making proposals for experiments at existing and forthcoming colliders of elementary particles.